1982
DOI: 10.1159/000166626
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Alterations in Pulmonary Gas Exchange during Acetate and Bicarbonate Hemodialysis

Abstract: We studied 10 patients during acetate and 10 patients during bicarbonate hemodialysis to assess changes of minute ventilation; oxygen consumption (VO2); and carbon dioxide production (VCO2) as well as pO2, pCO2 and pH. We also measured the extent of pulmonic shunting by administering 100% O2. Our studies revealed that VO2 increased significantly during acetate dialysis, while it decreased slightly during bicarbonate dialysis. Since VCO2decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Raja et al [ 12] observed a greater degree of hypoxemia when the concentration of acetate in the dialysate was 45 mM than when it was the usual value of 37 mM, suggesting that higher infusion rates of acetate -and, presumably, higher metabolic utilization of acetate -have a greater effect on reducing the respiratory quotient and increasing hypox emia. Eiser et al [20] similarly demonstrated a decreased respiratory quotient accompanied by hypoxemia and de creased minute ventilation during acetate dialysis; these authors also found, as had already been noted by Sher lock et al [15], that acetate dialysis resulted in increased consumption of oxygen which would obviously tend to compound the effect of decreased minute ventilation and be an added causal factor for hypoxemia. Interestingly, dialysis performed with C 0 2 bubbling in bicarbonatecontaining dialysate [20] was also accompanied by a drop in P a02 by an average of 10.3 mm Hg.…”
Section: Decreased Ventilation Due To Changes In the Endogenous Produmentioning
confidence: 55%
See 4 more Smart Citations
“…Raja et al [ 12] observed a greater degree of hypoxemia when the concentration of acetate in the dialysate was 45 mM than when it was the usual value of 37 mM, suggesting that higher infusion rates of acetate -and, presumably, higher metabolic utilization of acetate -have a greater effect on reducing the respiratory quotient and increasing hypox emia. Eiser et al [20] similarly demonstrated a decreased respiratory quotient accompanied by hypoxemia and de creased minute ventilation during acetate dialysis; these authors also found, as had already been noted by Sher lock et al [15], that acetate dialysis resulted in increased consumption of oxygen which would obviously tend to compound the effect of decreased minute ventilation and be an added causal factor for hypoxemia. Interestingly, dialysis performed with C 0 2 bubbling in bicarbonatecontaining dialysate [20] was also accompanied by a drop in P a02 by an average of 10.3 mm Hg.…”
Section: Decreased Ventilation Due To Changes In the Endogenous Produmentioning
confidence: 55%
“…Eiser et al [20] similarly demonstrated a decreased respiratory quotient accompanied by hypoxemia and de creased minute ventilation during acetate dialysis; these authors also found, as had already been noted by Sher lock et al [15], that acetate dialysis resulted in increased consumption of oxygen which would obviously tend to compound the effect of decreased minute ventilation and be an added causal factor for hypoxemia. Interestingly, dialysis performed with C 0 2 bubbling in bicarbonatecontaining dialysate [20] was also accompanied by a drop in P a02 by an average of 10.3 mm Hg. No change in respiratory quotient was noted with bicarbonate dialysis: both oxygen consumption and C 0 2 production decreased by about 10%.…”
Section: Decreased Ventilation Due To Changes In the Endogenous Produmentioning
confidence: 55%
See 3 more Smart Citations